A convenient, soil‐free method for the production of root nodules in soybean to study the effects of exogenous additives. (15th April 2019) - Roy Choudhury, Swarup; Johns, Sarah M.; Pandey, Sona
Abstract: Legumes develop root nodules that harbor endosymbiotic bacteria, rhizobia. These rhizobia convert nitrogen to ammonia by biological nitrogen fixation. A thorough understanding of the biological nitrogen fixation in legumes and its regulation is key to develop sustainable agriculture. It is well known that plant hormones affect nodule formation; however, most studies are limited to model legumes due to their suitability for in vitro, plate‐based assays. Specifically, it is almost impossible to measure the effects of exogenous hormones or other additives during nodule development in crop legumes such as soybean as they have huge root system in soil. To circumvent this issue, the present research develops suitable media and growth conditions for efficient nodule development under in vitro, soil‐free conditions in an important legume crop, soybean. Moreover, we also evaluate the effects of all major phytohormones on soybean nodule development under identical growing conditions. Phytohormones such as abscisic acid (ABA) and jasmonic acid (JA) had an overall inhibitory effect and those such as gibberellic acid (GA) or brassinosteroids (BRs) had an overall positive effect on nodule formation. This versatile, inexpensive, scalable, and simple protocol provides several advantages over previously established methods. It is extremely time‐ and resource‐efficient, does not require special training or equipment, and produces highly reproducible results. The approach is expandable to other large legumes as well as for other exogenous additives.